Risk Factors and Prognosis; An Effort to Predict the Severity of COVID-19 - Parisa Jooya; Neda Pouralimohamadi; Bisma Zulfaqar; Melika Arzhangzadeh; Seyed Amirhossein Shamszadeh; Behdad Tahayori (Shiraz University of Medical Sciences, 2023)
Background: Up to this time, screening for people infected with coronavirus disease 2019 (COVID-19) relies on clinical symptoms. As a result, our study focused on establishing a relationship between clinical manifestations, risk factors, and the prognosis of COVID-19 for prompt intervention.Methods: This cross-sectional study was performed on patients with positive COVID-19 tests in Shiraz, Iran, from 2020 through 2021. Patients were randomly selected from those registered as COVID-19 positive in various family clinics affiliated with Shiraz University of Medical Sciences Health Centers. A telephone interview was conducted to gather necessary data about the clinical symptoms of 401 patients, their risk factors, and their prognosis of the disease in two weeks.Results: Body pain, followed by fever, were the most reported symptoms. Except for dyspnea that was related to hospitalization, no relation was found between initial clinical symptoms and hospitalization or 2-week recovery. We observed a statistically significant difference between different blood groups of patients concerning their rate of hospitalization and recovery after two weeks. A significant relationship between hypertension and hospitalization was seen.Conclusion: Body pain, fever, certain demographic aspects (such as older age), and comorbidities like hypertension showed strong associations with the severity and prognosis of COVID-19. Our results add to the growing body of evidence suggesting blood type may play a role in the prognosis of COVID-19.